(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article is about the research work and scientific innovation of modern Russian scientists on labor motivation. In addition, the article contains the recommendations of scientists on the application of these innovations to life.